An alternative method for serum protein depletion/enrichment by precipitation at mildly acidic pH values and low ionic strength. Issue 11 (13th March 2015) - Henning, Ann‐Kristin; Albrecht, Dirk; Riedel, Katharina; Mettenleiter, Thomas C.; Karger, Axel
<x xml:space="preserve">Abstract</x> Serum proteome analysis is severely hampered by the extreme dynamic range of protein concentrations, but tools for the specific depletion of highly abundant serum proteins lack for most farm and companion animals. A well‐established alternative strategy to reduce the dynamic range of plasma protein concentrations, treatment with combinatorial peptide ligand libraries (CPLL), is generally applicable but requires large amounts of sample. Therefore, additional depletion/enrichment protocols for plasma and serum samples from animals are desirable. In this respect, we have tested a protein precipitate that formed after withdrawal of salt from human, bovine, or porcine serum at pH 4.2. The bovine sample was composed of over 300 proteins making it a potential source for biomarker discovery. Precipitation was highly reproducible and the concentrations of albumin and other highly abundant serum proteins were strongly reduced. In comparison to the CPLL treatment, precipitation did not introduce any selection bias based on hydrophathy or pI. However, the composition of both preparations was partially complementary. Salt withdrawal at pH 4.2 is suggested as additional depletion/enrichment strategy for serum samples. Also, we point out that the removal of precipitates from serum samples under the described conditions bears the risk of losing a valuable protein fraction.